Strengthening The Family Welfare Empowerment And Resilience On Jombang Regency - Suharsono, Judi; Candra, Sulis (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Family welfare empowerment on Jombang Regency are needed to increase support citizens, especially with decreasing economic growth. The purpose of this community service activities was to increase the family welfare and resilience entering the endemic era of Covid-19. Method used in carrying out the communication activity was Effective Communication Strategy and combined with Ethnohypnosis method. Blending method with Ethnohypnosis allows participants to carry out positive messages at the subconscious level. The steps of method use in this community service activity overall comprises six stages, beginning with: Observation, identification, pre-test, socialization, workshop, post-test. The data was taken from 51 sample from the total of 455 population, using purposive sampling method. The result show that family welfare could be attained by coordinating all stakeholders and the focus of attention based on age period as existed in Tri Bina (BKB, BKR, and BKL) programs. High participant numbers of family welfare organization would significantly impact the overall aspects of family welfare, empowerment, and resilience; especially in the more challenging era as the aftermath of Covid-19 pandemic. Education proposed to be mainly contributing in taking family resilience guarantee into account, where lower education background causing lower awareness on how to build and maintain family welfare.